Accuracy of otoscopy, tympanic membrance mobility and tympanometry in the diagnosis of otitis media with effusion - KC, S; Guragain, RPS; Sinha, BK (Journal of Institute of Medicine Nepal, 2007)
Background: To determine the accuracy of otoscopy, pneumatic otoscopy and tympanometry in the diagnosis of otitis media with effusion. Materials and Methods: A total of 71 patients (121 ears) suffering from Otitis Media with Effusion (OME) diagnosed clinically were subjected to myringotomy and ventilation tube insertion (VTI). The finding of presence of fluid in middle ear after myringotomy was correlated with Tympanic Membrane (TM) color, fluid level, air bubble, TM mobility and tympanometric curve recorded preoperatively. Results: Otoscopic findings revealed pink TM in 78.5%, prominent landmarks in 98.3%, generalized retraction 73.6%, fluid level in 14% and air bubble in 2.5% of cases. On pneumatic otoscopy, decreased or absent mobility was found in 85.1%. Tympanometry with ‘B’ curve was the most sensitive finding (98.9%), whereas pneumatic otoscopy was found to be the most specific amongst all the three tools. Combination of tympanometry with either otoscopy or pneumatic otoscopy or combination of all three modalities was found to be highly significant . Conclusion: Tympanometry is the most sensitive tool for the diagnosis of OME and combination of tympanometry with either otoscopy or pneumatic otoscopy is highly significant. Key words: otitis media with effusion (OME), pneumatic otoscopy, tympanometry The full text of this paper is available at Journal of Institute of Medicine website